Oxidation-Triggerable Liposome Incorporating Poly(Hydroxyethyl Acrylate-co-Allyl methyl sulfide) as an Anticancer Carrier of Doxorubicin - Kim, Jin Ah (Cancers (Basel), 2020)
Since cancer cells are oxidative in nature, anti-cancer agents can be delivered to cancer cells specifically without causing severe normal cell toxicity if the drug carriers are designed to be sensitive to the intrinsic characteristic. Oxidation-sensitive liposomes were developed by stabilizing dioleoylphosphatidyl ethanolamine (DOPE) bilayers with folate-conjugated poly(hydroxyethyl acrylate-co-allyl methyl sulfide) (F-P(HEA-AMS)). The copolymer, synthesized by a free radical polymerization, was surface-active but lost its surface activity after AMS unit was oxidized by H(2)O(2) treatment. The liposomes with F-P(HEA-AMS) were sensitive to H(2)O(2) concentration (0%, 0.5%, 1.0%, and 2.0%) in terms of release, possibly because the copolymer lost its surface activity and its bilayer-stabilizing ability upon oxidation. Fluorescence-activated cell sorting (FACS) and confocal laser scanning microscopy (CLSM) revealed that doxorubicin (DOX)-loaded liposomes stabilized with folate-conjugated copolymers markedly promoted the transport of the anti-cancer drug to cancer cells. This was possible because the liposomes were readily translocated into the cancer cells via receptor-mediated endocytosis. This liposome would be applicable to the delivery carrier of anticancer drugs.